Human Capital, Resource Constraints and Intergenerational Fairness - Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
This paper studies an endogenous growth model with human capital, exhaustible resources, and overlapping generations. Under laissez-faire, higher study time reduces depletion rates by increasing the share of re- sources that present generations are willing to sell to successors. However, selfish behavior may prevent competitive sustained growth, and implement- ing utilitarian allocations generally induces optimal-and-sustainable paths. It is shown that: (i) raising study time and decreasing resource depletion are always complementary targets in optimal policies; (ii) growth effects are stronger the lower the optimal share of exploited resources; (iii) gener- ational welfare gains from optimal policies are delayed by faster depletion and, contrary to intuition, anticipated by lower social discount rates.
Keywords: H30; Q01; Q20; 330; Endogenous Growth; Exhaustible Resources; Human Capital; Over- lapping Generations; Intergenerational Fairness; Sustainability; Endogenes Wachstumsmodell; Humankapital; Erschöpfbare Ressourcen; Gerechtigkeit; Overlapping Generations; Theorie